(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
هدف البحث إلى التعرف على دور مديرة الروضة في تطوير أداء معلمات رياض الأطفال في تنمية مهارات الأطفال اللغوية من وجهة نظر معلمات رياض الأطفال. والتعرف على الفروق بين متوسطات إجابات أفراد عينة البحث (معلمات رياض الأطفال) على استبانة البحث وفقاً لمتغيرات البحث: (الدورات التدريبية، المؤهل العلمي، سنوات الخبرة). واستخدم الباحث المنهج الوصفي التحليلي، وتكونت عينة البحث من (218) معلمة من معلمات رياض الأطفال في محافظة دمشق، واستخدم الباحث استبانة من إعداده وتكونت من (64) بنداً موزعة على أربعة أبعاد، وخلص الباحث إلى النتائج التالية: - توجد فروق ذات دلالة إحصائية بين متوسطات درجات معلمات رياض الأطفال على استبانة البحث تبعاً لمتغير عدد الدورات التدريبية لصالح المعلمات اللواتي خضعن لـ (6) دورات تدريبية فأكثر. - توجد فروق ذات دلالة إحصائية بين متوسطات درجات معلمات رياض الأطفال على استبانة البحث تبعاً لمتغير المؤهل العلمي لصالح المعلمات اللواتي يحملن مؤهل علمي: دبلوم تأهيل تربوي فأكثر. - توجد فروق ذات دلالة إحصائية بين متوسطات درجات معلمات رياض الأطفال على استبانة البحث تبعاً لمتغير عدد سنوات الخبرة لصالح المعلمات اللواتي لديهن سنوات خبرة عدد (5) سنوات فأقل. The goal of research is to identify the role of director of kindergarten in the development of the performance of kindergarten teachers in the development of children’s language skills from the perspective of kindergarten teachers. and to identify the differences between the averages Answers members of the research sample (kindergarten teachers) to identify research and according to the research variables: (training, qualification, years of experience). The researcher used the descriptive analytical method, and the research sample consisted of (218) teacher of the kindergarten teachers in the province of Damascus, and the researcher used the questionnaire prepared and consisted of 64 items divided into four dimensions, the researcher concluded the following results: - There are significant differences between the Scores mean of the kindergarten teachers to identify research variable depending on the number of training courses for teachers who have undergone (6) training courses and more. - There are significant differences between the Scores mean of the kindergarten teachers to identify research variable depending on qualification for teachers who become pregnant qualification diploma or more. - There are significant differences between the Scores mean of the kindergarten teachers to identify research variable depending on the number of years of experience for the benefit of teachers who have a number of years experience (5) years or less.